2014
DOI: 10.3390/w6030564
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrograph-Based Sediment Availability Assessment: Implications for Mississippi River Sediment Diversion

Abstract: Abstract:The Mississippi River Delta Plain has undergone substantial land loss caused by subsidence, relative sea-level rise, and loss of connectivity to the Mississippi River. Many restoration projects rely on diversions from the Mississippi River, but uncertainty exists about the timing and the amount of actually available sediment. This study examined long-term (1980-2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…However, Rosen and Xu [21] contradicted this trend by suggesting that suspended sediment input has slightly increased in the river for the recent two decades (from 1990 to 2010), although no statistical significance was found. Our findings for sand transport (the courser sediment fraction) are identical with Rosen and Xu [21] as we also found a stronger increasing trend in sand loads starting from 1990-the average annual sand load from 1990 to 2013 (30˘5.4 MT) was clearly higher than that during 1973 and 1989 (23˘4.1 MT). The higher sand transport in the past two decades has mainly resulted from the increased discharge during the same period of time.…”
Section: Long-term Trend Of Sand Loads In the Lmmrmentioning
confidence: 98%
See 2 more Smart Citations
“…However, Rosen and Xu [21] contradicted this trend by suggesting that suspended sediment input has slightly increased in the river for the recent two decades (from 1990 to 2010), although no statistical significance was found. Our findings for sand transport (the courser sediment fraction) are identical with Rosen and Xu [21] as we also found a stronger increasing trend in sand loads starting from 1990-the average annual sand load from 1990 to 2013 (30˘5.4 MT) was clearly higher than that during 1973 and 1989 (23˘4.1 MT). The higher sand transport in the past two decades has mainly resulted from the increased discharge during the same period of time.…”
Section: Long-term Trend Of Sand Loads In the Lmmrmentioning
confidence: 98%
“…These regimes were further Figure 1. Study area map (modified from Rosen and Xu [21]) showing the location of the LmMR at Tarbert Landing (TBL) (USGS Station ID 07295100 and USACE Gage ID 01100). MR and AR denote the courses of the Mississippi and Atchafalaya Rivers respectively; ORCS is the Old River Control Structure; "Sim" denotes Simmesport (USGS Station ID 07381490) site of the Atchafalaya River; RRL is Red River Landing, the gauging station for USGS just below TBL consisting of river stage records and CAR denotes Carrolton, New Orleans.…”
Section: Noaa's River Stages and Their Corresponding Flow Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same location, a report by the U.S. Army Corps of Engineers (USACE) [12] gave an average annual SSL of 134 MT for the decade 1989-1998 and a nearly 10% reduced load (123 MT) for the following decade. In a recent study, however, Rosen and Xu [13] reported an average annual suspended sediment load of 126 MT for the three decades of 1980-2010, with an insignificant but slightly increasing trend from 1990 to 2010. For the Mississippi River's largest distributary, the Atchafalaya River at Simmesport, Xu [14] reported an average annual suspended sediment load of 64 MT over the period , while the USACE report [12] gave an annual SSL of 48 MT for 1999-2008 and 75 MT for [1989][1990][1991][1992][1993][1994][1995][1996][1997][1998].…”
Section: Introductionmentioning
confidence: 99%
“…Recent works by Rosen and Xu (2014) using a similar approach is a sediment availability assessment for the Mississippi River using stage hydrograph, while Ndomba (2013) used the Pacific Southwest Inter-Agency Committee (PSIAC) model for sediment yields estimation in ungauged catchments in Tanzania, and Curran- Cournane et al (2013) used sampled storm events and the sediment yield events in Auckland.…”
mentioning
confidence: 99%